Irradiation dose response under hypoxia for the application of the sterile insect technique in Drosophila suzukii. - Fabiana Sassù; Katerina Nikolouli; Rui Pereira; Marc J B Vreysen; Christian Stauffer; Carlos Cáceres (PLoS ONE)
Treating insects with a lower oxygen atmosphere before and during exposure to radiation can mitigate some of the negative physiological effects due to the irradiation. The irradiation of pupae under oxygen-reduced environment such as hypoxia or anoxia is routinely used in the sterile insect technique (SIT) of some tephritid species as it provides radiological protection. This treatment allows to have the sterile pupae already in sealed containers facilitating the shipment. SIT is an environment friendly control tactic that could be used to manage populations of Drosophila suzukii in confined areas such as greenhouses. The objectives of this study were to assess the effect of irradiation on the reproductive sterility in D. suzukii males and females under low-oxygen atmosphere (hypoxia) and atmosphere conditions (normoxia). Additionally, we assessed the differences in radiological sensitivity of pupae treated under hypoxia and normoxia conditions. Finally, the effect on emergence rate and flight ability of the irradiated D. suzukii adults exposed to doses that induced >99% of sterility were assessed. Pupae needed a 220 Gy irradiation dose to achieve >99% of egg hatch sterility in males irrespective of the atmosphere condition. For females the same level of sterility was achieved already at 75 Gy and 90 Gy for the normoxia and hypoxia treatments, respectively. Radiation exposure at 170 and 220 Gy under the two atmosphere treatments did not have any effect on the emergence rate and flight ability of D. suzukii males and females. Therefore, hypoxia conditions can be used as part of an area-wide insect pest management program applying SIT to facilitate the protocols of packing, irradiation and shipment of sterile D. suzukii pupae.